Syphilis prevalence among women in the prison system of a northeastern Brazilian capital - Telma Maria Evangelista de Araújo; Augusto Cezar Antunes de Araujo Filho; Karla Vivianne Araújo Feitosa (Universidade Federal de Goias, 2015)
The aim of this study was to investigate the prevalence of syphilis and associated factors in inmates of the women's prison of Teresina, Piauí, Brazil. This cross-sectional study was conducted in November 2013. The population consisted of inmates from the referred penitentiary (n=131). Data were collected through a form composed of closed-ended and mixed questions. The mean age was 33.1 years, 60.3% affirmed not having a stable relationship, and 93.1% had children. Alcohol use was reported by 70.8%, and the use of illicit drugs, by 56.2%. It was evidenced that 38.5% of women never use a condom during sexual intercourse, and that 62.2% do not know how the transmission of syphilis happens. The high prevalence of syphilis, 25.2%, is statistically associated with marital status, illicit drug use and their consumption before sex, demonstrating that unfavorable socioeconomic conditions are important risk and vulnerability factors to sexually transmitted diseases.